Budget Abuse as a Form of Corruption - Kawuryan, Angelica Ari Pramesti; Alhadi, Muhammad Nurcholis; Rahayuningsih, Uut (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: This study examines the form of criminal liability of public officials involved in corruption crimes, particularly in the misuse of state budgets. The case analyzed is Decision Number 15/Pid.Sus-TPK/2020/PN.MNK involving Ahmad Afit Rumagesan, Chairman of the Fakfak District Parliament for the 2009–2014 period.Purposes of the Research: This study underscores the importance of strengthening oversight in public financial management to prevent future budget misuse.Methods of the Research: This research applies a normative juridical method with a case study approach.Findings of the Research: The findings indicate that the defendant was proven to have misused the treasurer's cash funds for personal purposes without a legitimate legal basis, resulting in a state loss of IDR 432,425,000. In passing the verdict, the judge considered the state's financial loss, the defendant's role, and the absence of good faith to return the funds.